PENINGKATAN PERCAYA DIRI SISWA MELALUI MODEL THINK-PAIR-SHARE (TPS) PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Yen Kristina Situmeang; Mariani Meri Lumban Gaul (STKIP Pesisir Selatan, 2026)
This study aims to improve students’ self-confidence through the implementation of the Think Pair Share (TPS) learning model in Catholic Religious Education for class VIII-1 at SMP Swasta RK Deli Murni Diski. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants of this study were 35 students. Data were collected through observation and documentation techniques and analyzed descriptively to identify improvements in students’ self-confidence during the learning process. The findings revealed that the implementation of the Think Pair Share (TPS) learning model successfully improved students’ self-confidence, as indicated by increased courage in expressing opinions, active participation, enthusiasm during discussions, and involvement in classroom learning activities. The average percentage of students’ self-confidence increased from 77.80% in Cycle I to 93.19% in Cycle II. The novelty of this study lies in the implementation of the Think Pair Share (TPS) model to strengthen students’ affective development, particularly self-confidence, in Catholic Religious Education at the junior high school level.